Prediction of Future Mortality in China under the New Demographic Norm - chen, cuixia (Advances in Social Sciences Research Journal, 2017)
In recent years, China's population life expectancy into the rapid growth stage, this population growth caused by the rapid growth of a series of risks known as longevity risk. The increase in life expectancy concerns the future survival of individuals, as well as the profitability and solvency of commercial insurers, and most importantly, the impact on pension plans throughout the country. Therefore, it is necessary to accurately predict future mortality in China at this stage. In this paper, the Lee-Carter model least square method is used to estimate the parameters. Secondly, according to the Box-Jenkins method, the ARIMA model is used to fit the forecasting of life expectancy and life expectancy.